سُنن ِ الٰہیہ اورتکوینی قوانین : قرآنی آیات کی روشنی میں تعارفی مطالعہ - Muti ur Rehman Bhutto; Mustafeez Ahmad Alvi (Pakistan Journal of Islamic Research)
The scientific knowledge has discovered that a set of laws govern the whole universe; ranging from a particle of sand to a galaxy of stars and planets.  According to the scientists, the Nature has prescribed these laws, therefore, the laws are named as Laws of Nature. The premise has its own empirical evidence and verifiable experiments. According to the knowledge revealed to human through Prophets, the universe is governed by God Almighty; therefore He is the only Creator and Master of the nature and of its laws. The Holy Qur’an, being the last and latest revealed book has explained the whole universe as creation of Allah Almighty who governs it through His principles and rules. The laws governing the creation are Qwaneen e Takween and the laws governing human life and activity are named Sunan Ilahiyah. The following research paper, is an effort to discover different interpretations and the major distinctions of these two terms in the light of exegesis of the Qur’anic verses.